Developing an Archetypal Framework for the Inno-preneurial University: A Strategic Model for Vietnam - Huu Thanh Chung, Nguyen; Thi Thu Huong, Dang; Thi Thanh Tu, Tran; Huu Duc, Nguyen (VNU Journal of Science: Policy and Management Studies, 2025)
Abstract: Higher education is undergoing a profound transformation driven by the knowledge economy, digitalization, and the demand for sustainable development. Traditional university models are increasingly inadequate in addressing these emerging requirements. This study systematizes the evolution of contemporary university models and develops a theoretical framework consisting of seven archetypes of entrepreneurial and innovation-oriented universities: the Research-preneurial, Techni-preneurial, Inno-preneurial, Commerce-preneurial, Socio-preneurial, Sustainable-preneurial, and Digital-preneurial University. Through international comparison, theoretical analysis, and an examination of Vietnam’s higher education context, the study evaluates the suitability of each archetype and determines the most viable strategic direction for Vietnam. Findings show that several archetypes are not feasible for broad implementation in Vietnam due to substantial resource demands or high levels of specialization. The analysis identifies the Inno-preneurial University as the most appropriate model, given its capacity to integrate interdisciplinary research, innovation, knowledge transfer, digital transformation, social entrepreneurship, and sustainability—key priorities in national development strategies. The study further emphasizes that adopting this model requires comprehensive reforms in governance, financing, organizational structures, innovation culture, and university–industry–community partnerships. The Inno-preneurial University thus offers a strategic pathway for enhancing the role of Vietnamese universities in socioeconomic development and global scientific competitiveness. Keywords:   Inno-preneurial University; Entrepreneurial University; Elite University; Flagship University; University Archetypes.